Optical radiation and matter - Brecha, Robert J.; O'Hare, J. Michael (IOP (Series). Release 21., 2021)
Optical Radiation and Matter provides a deeper look at electricity and magnetism and the interaction of optical radiation with molecules and solid materials. The focus is on developing an understanding of the sources of light, how light moves through matter, and how external electric and magnetic fields can influence the way light waves propagate through materials.